Comparison of rhizosphere and endophytic microbial communities of Chinese leek through high-throughput 16S rRNA gene Illumina sequencing - Yong-hong HUANG (Journal of Integrative Agriculture, 2018)
Chinese leek (Allium tuberosum Rottler ex Sprengel) is a common vegetable in China. In our previous study, Chinese leek in rotation was found to have significant antifungal and nematicidal activity. This study's aim was to investigate the potential antifungal and nematicidal activity associated with rhizosphere or endophytic microbes of Chinese leek. Thus, a total of 79 261 high-quality sequences were obtained from Chinese leek rhizosphere soil, leaf and root samples. In the rhizosphere soil, the bacterial community comprised five dominant phyla: Proteobacteria (37.85%), Acidobacteria (10.99%), Bacteroidetes (8.24%), Cyanobacteria (7.79%) and Planctomycetes (7.1%). The leaf and root bacterial communities comprised two dominant phyla: Cyanobacteria (83.42% in leaf and 75.44% in root) and Proteobacteria (14.75% in leaf and 21.04% in root). Microbial diversity, richness and evenness in the rhizosphere soil bacterial community were higher than that in the endophytic bacterial communities. The rhizosphere bacterial community was significantly different from the endophytic bacterial communities. The endophytic bacterial communities from the leaf and the root were slightly, but not significantly different from each other. This study's findings would contribute to the isolation and identification of nematicidal and antifungal bacterial communities in Chinese leek.